Kinetic simulations of scrape-off layer physics in the DIII-D tokamak. (August 2017) - Churchill, R.M.; Canik, J.M.; Chang, C.S.; Hager, R.; Leonard, A.W.; Maingi, R.; Nazikian, R.; Stotler, D.P.
Highlights: Kinetic simulations of scrape-off layer transport of DIII-D H-mode plasma. Plasma density and ion temperature show significant poloidal variation, likely due to ion orbit loss. Parallel ion flow levels seen in experiment are seen in the simulation. Sheath potential is elevated due to kinetic features in particle distribution function. Abstract: Simulations using the fully kinetic code XGCa were undertaken to explore the impact of kinetic effects on scrape-off layer (SOL) physics in DIII-D H-mode plasmas. XGCa is a total- f, gyrokinetic code which self-consistently calculates the axisymmetric electrostatic potential and plasma dynamics, and includes modules for Monte Carlo neutral transport. Fluid simulations are normally used to simulate the SOL, due to its high collisionality. However, depending on plasma conditions, a number of discrepancies have been observed between experiment and leading SOL fluid codes (e.g. SOLPS), including underestimating outer target temperatures, radial electric field in the SOL, parallel ion SOL flows at the low field side, and impurity radiation. Many of these discrepancies may be linked to the fluid treatment, and might be resolved by including kinetic effects in SOL simulations. The XGCa simulation of the DIII-D tokamak in a nominally sheath-limited regime show many noteworthy features in the SOL. The density and ion temperature are higher at the low-field side, indicative of ion orbit loss. The SOL ion Mach flows are at experimentally relevant levels ( Mi ∼ 0.5), with similar shapes and poloidal variation as observed in various tokamaks. Surprisingly, the ion Mach flows close to the sheath edge remain subsonic, in contrast to the typical fluid Bohm criterion requiring ion flows to be above sonic at the sheath edge. Related to this are the presence of elevated sheath potentials, e Δ Φ / T e ∼ 3 − 4, over most of the SOL, with regions in the near-SOL close to the separatrix having eΔΦ / Te > 4. These two results at the sheath edge are a consequence of non-Maxwellian features in the ions and electrons there.